2023
DOI: 10.1001/jamanetworkopen.2023.29678
|View full text |Cite
|
Sign up to set email alerts
|

Four-Component Recombinant Protein–Based Vaccine Effectiveness Against Serogroup B Meningococcal Disease in Italy

Lorenzo Lodi,
Federica Barbati,
Daniela Amicizia
et al.

Abstract: ImportancePopulation-based data on the 4-component recombinant protein–based (4CMenB) vaccine effectiveness and reduction in incidence rate ratios (IRRs) are continuously needed to assess vaccine performance in the prevention of serogroup B invasive meningococcal disease (IMD).ObjectiveTo assess the effectiveness and reduction in IRRs associated with the 4CMenB vaccine in the pediatric population in 6 regions in Italy.Design, Setting, and ParticipantsThis retrospective cohort screening study and case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(100 reference statements)
0
3
0
Order By: Relevance
“… 19 A recent retrospective cohort screening study, carried out in Italy, reported that earlier vaccination with the four-component MenB vaccine (4CMenB) may lead to greater protection against meningococcal infection. 9 Pellegrino et al 20 also reported that co-administration of DTaP-IPV-HB-Hib, PCV, and MenC vaccines has led to increased vaccine coverage in the LHU of Cuneo-1, from 47% to 65%, in only one year of implementation. According to evidence from experience in the United Kingdom, co-administration of such vaccines does not affect vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 A recent retrospective cohort screening study, carried out in Italy, reported that earlier vaccination with the four-component MenB vaccine (4CMenB) may lead to greater protection against meningococcal infection. 9 Pellegrino et al 20 also reported that co-administration of DTaP-IPV-HB-Hib, PCV, and MenC vaccines has led to increased vaccine coverage in the LHU of Cuneo-1, from 47% to 65%, in only one year of implementation. According to evidence from experience in the United Kingdom, co-administration of such vaccines does not affect vaccine efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to the updated co-administration strategy outlined in the CIC could provide many advantages, such as fewer vaccination appointments during the first year of life, completion of the primary vaccination cycle in two sessions (compared with the standard of four), and thereby earlier vaccination, which may provide greater protection against some diseases. 8 , 9 Similar vaccination strategies have also been used previously in the United Kingdom and Portugal. 10 , 11 In the United Kingdom, vaccine co-administration led to no reductions in vaccine coverage or efficacy, and no negative impact on the overall tolerability of the vaccines.…”
Section: Introductionmentioning
confidence: 97%
“… 74 More recently, 4CMenB vaccine effectiveness against MenB disease in fully immunized children in three Italian regions (Tuscany, Veneto, and Piedmont) was found to be 94.9% (95% CI: 83.1–98.4) by a screening method and 91.7% (24.4–98.6) in six regions (Tuscany, Veneto, Piedmont, Apulia, Liguria, and Sicily) by a case-control method. 75 Almost 20% of the cases in unvaccinated children were among infants too young to be vaccinated, suggesting earlier vaccination may prevent more MenB disease cases.…”
Section: Real World Effectiveness and Impact Against Menb Diseasementioning
confidence: 99%